2019
DOI: 10.1017/s1368980019002507
|View full text |Cite
|
Sign up to set email alerts
|

Does message framing matter for promoting the use of nutritional warnings in decision making?

Abstract: Objective:To evaluate the impact of message framing on attitudes towards messages aimed at promoting the use of nutritional warnings, behavioural intention and actual behaviour, evaluated through visual attention to nutritional warnings and the choice of a snack product during a real choice task.Design:Following a between-subjects design, participants were exposed to loss-framed nutrition messages, gain-framed nutrition messages or non-nutrition-related messages (control group). After evaluating the messages, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
1
9
0
2
Order By: Relevance
“…These results are in agreement with Ares, Machín, et al (2020), who reported that Uruguayan citizens frequently mentioned expressions related to the health benefits of avoiding products with excessive content of sugar, fat, and sodium as part of a communication campaign to encourage the use of nutritional warnings in decision making, whereas expressions related to avoiding the negative consequences of consuming such products were less frequently mentioned. Similarly, Vidal et al (2019), reported a more positive attitude toward gain-framed messages compared with loss-framed messages. In the context of health promotion, Rothman and Salovey (1997) and Gallagher and Updegraff (2012) concluded that gain-framed messages tend to be superior to loss-framed messages for promoting behaviors that are not perceived as particularly risky.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…These results are in agreement with Ares, Machín, et al (2020), who reported that Uruguayan citizens frequently mentioned expressions related to the health benefits of avoiding products with excessive content of sugar, fat, and sodium as part of a communication campaign to encourage the use of nutritional warnings in decision making, whereas expressions related to avoiding the negative consequences of consuming such products were less frequently mentioned. Similarly, Vidal et al (2019), reported a more positive attitude toward gain-framed messages compared with loss-framed messages. In the context of health promotion, Rothman and Salovey (1997) and Gallagher and Updegraff (2012) concluded that gain-framed messages tend to be superior to loss-framed messages for promoting behaviors that are not perceived as particularly risky.…”
Section: Discussionmentioning
confidence: 92%
“…Wirtz and Kulpavaropas (2014) reported that although participants preferred gain-framed messages over negatively framed messages, the latter resulted in higher behavioral intentions. Similarly, Vidal et al (2019) reported that participants preferred gain-frame over loss-frame messages. However, participants exposed to loss-frame messages tended to pay more visual attention to nutritional warnings when choosing a snack product and select more healthful products than those exposed to gain-frame messages.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, reformulated products without NWLs have a big chance of being purchased [ 15 , 17 ]. This chance is because the NWL acts as a brake on the appetizing signals of processed foods, as the NWL message increases people’s visual attention and allows an informed choice of food, focusing on improving diet quality and health status [ 50 , 51 , 52 ]. However, there are consumers for whom NWLs have little effect on their food choices [ 41 ], such as the male gender and the low-income socioeconomic group.…”
Section: Discussionmentioning
confidence: 99%
“…The way people process health-related information is not completely rational [6,7]; this indicates that the sole examination of media presentations cannot precisely measure the real persuasive effects of messages [8,9]. People's decision-making preferences are also affected by how information is presented [10][11][12]. According to framing effect theory, different presentations of health-related information can affect individuals' decision-making preferences.…”
Section: Introductionmentioning
confidence: 99%